Being Prey: Dismantling the Emplacement/Displacement Dualism - Booth, Kate Isabel (The Trumpeter, 2013)
Emplacement and displacement can be presented as experiences that lie in direct opposition to each other. To experience emplacement is to be immersed within the rich nuances of a place; it is to embody some kind of authentic existence that sees the self and the place inhabited as deeply aligned. The experience of displacement is to feel oneself as so disconnected from the intricacies of a place as to assume that such intricacies are non-existent; the self is unable to find a home within a place as the place is experienced as devoid of meaning and significance. In this paper I challenge this dualistic account of emplacement and displacement using Val Plumwood’s observations pertaining to dualisms and dismantling dualisms. I explore Plumwood’s account of ‘Being Prey’ as an example of how a non-dualistic understanding of ‘placement’ may emerge.